Physicochemical and Fatty Acid Evalution of Some Shea Butter Samples in Nigeria (Global Journal of Science Frontier Research, 2023)
Shea butter is a significant source of fat in the diet of many rural dwellers in Nigeria. It is produced from the seeds of Vitellaria paradoxa L tree. Its suitability as dietary fat or use in cosmetic industry is greatly influenced by its physicochemical properties and fatty acid composition. This study aimed at determining the physicochemical properties and fatty acid profile of shea butter found in Nigeria as a possible source of industrial raw material for the production of stearic acid. The physicochemical analyses results showed that the saponification value of the shea butter samples ranged from 174.55 mg/KOH/g -200.97 mg/KOH, while iodine value is from 42.22 g/100g -98.46 g/100g, the unsaponifiable matter ranged from 2.32 -10.55 % and peroxide value ranged from 8.14 meq/kg -19.66 meq/kg.
Keywords: shea butter; physicochemical; fatty acid and vitellaria paradoxa